2004
DOI: 10.1111/j.1651-2227.2004.tb02696.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced case fatality among hospitalized children during a war in Guinea‐Bissau: a lesson in equity

Abstract: The decline in case fatality could be explained neither by a general decline in childhood mortality nor by changes in recruitment or discharge policy. The decline was therefore most likely due to improved treatment as a result of better availability of drugs funded by humanitarian aid and the presence of dedicated staff, which was offered relief food as compensation. Interventions improving case management may have a proportionately larger effect for poor families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 10 publications
1
20
0
1
Order By: Relevance
“…The interviewees, including military authorities, were willing to respond to questions addressing human resources, functioning of health facilities and HIV/AIDS issues. Our observation that health-related research can be pursued in the aftermath of an armed conflict, which indeed facilitates assessment and quantification of conflict impacts, is consistent with recent reports from other conflict zones across Africa (Ahuka et al , 2004;DeLargy & Alakbarov, 2004;Larsen et al , 2004;O'Heir, 2004;Sodemann et al , 2004;Tangermann et al , 2000). Perhaps the most extreme example arises from the first nationwide cross- sectional survey carried out 18 months after the March 2003 invasion of Iraq.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The interviewees, including military authorities, were willing to respond to questions addressing human resources, functioning of health facilities and HIV/AIDS issues. Our observation that health-related research can be pursued in the aftermath of an armed conflict, which indeed facilitates assessment and quantification of conflict impacts, is consistent with recent reports from other conflict zones across Africa (Ahuka et al , 2004;DeLargy & Alakbarov, 2004;Larsen et al , 2004;O'Heir, 2004;Sodemann et al , 2004;Tangermann et al , 2000). Perhaps the most extreme example arises from the first nationwide cross- sectional survey carried out 18 months after the March 2003 invasion of Iraq.…”
Section: Discussionsupporting
confidence: 90%
“…The importance of collaborative efforts between governments, UN agencies, national and international organisations and NGOs and a more strategic positioning of UN agencies and NGOs has been stressed before (O'Heir, 2004;Salama et al , 2004). A recent study carried out in Guinea-Bissau, for example, documented a decline in case fatality among hospitalised children during an armed conflict, which had been explained by a strengthened health system, including improved access to effective care and treatment (Sodemann et al, 2004). Another study carried out in Sierra Leone that focused on military personnel and commercial sex workers, showed that sound HIV/AIDS awareness campaigns during post-conflict periods can significantly reduce the transmission of HIV (Larsen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…8 This was not explained by a general decline in mortality during the war, and children admitted to hospital during the war did not seem to be less sick or more advantaged socioeconomically. Mortality in the community increased by 34% during the war.…”
Section: Introductionmentioning
confidence: 97%
“…At krige ofte afslører dårlige sundhedsforhold, der var tilstede før krigen, viste sig i Bissau, Guinea-Bissau, under den vaebnede konflikt 1998(Sodemann et al 2004 …”
Section: Krig Er Afslørendeunclassified